Two-step hot isostatic pressing densification achieved non-porous fully-densified wood with enhanced physical and mechanical properties - J. C. Maturana; P. Guindos; J. Lagos; C. Arroyave; F. Echeverría; E. Correa (Scientific Reports, 2023)
Abstract A new two-step densification method for wooden materials entitled hot isostatic pressing (HIP) is proposed. This method has the advantage over previous densification methods that can achieved almost the full densification of wood, reaching values up to 1.47 kg/m3, which exceeds any value ever reported for a hardwood species. Furthermore, it can preserve about 35% of the original volume, in comparison to other methods which typically can preserve only 20% of the volume. Although not tested in this investigation, in principle, the HIP method should be capable of densifying any shape of wood including circular and tubular cross sections because the main densification mechanism is based on gas pressure that is equally exerted in the entire surface, rather than localized mechanical compression, which can only be effective with rectangular cross sections. In the first stage of the two-step proposed method, the compressive strength of the anatomical wood structure is reduced by delignification, and, in the second, a full densification is achieved by hot isostatic pressing under argon atmosphere. Three tropical hardwood species with distinct anatomical characteristics and properties were used to test the method. The HIP-densified wood’s microstructural, chemical, physical, and mechanical properties were assessed. Apart from the high densification values and volume preservation, the results indicate that proposed method was effective for all the tested species, showing homogenous density patterns, stable densification without noticeable shape recovery, and enhanced mechanical properties. Future research should test the HIP method in softwoods and consider the ring orientation in order to enhance the control of the densified geometry.